Pengembangan Lembaga Pendidikan Islam di Indonesia: Analisis Kritis Peluang dan Tantangan - Khojir, Khojir (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2011)
Institutions of Islamic education in Indonesia today have been growing in many variety. Growth and development are inseperable from the opportunities that surround it. Opportunities of Islamic education development in Indonesia is very large. They are muslim peoples in Indonesia who converted to Islam a-majority, having the concept of a mature theologis, the government is allowing the public to develop the varied Islamic education. However, there are also several challenges, the first is globalization and the development of science and technology, so that Islamic education must adapt to these developments. The Second is academic cultures that are less rooted in academic circles as well as educational practitioners. The third, is the challenge of education among the Reformers, who has always argued that Islamic education is identical with the old-fashioned and backward education. Therefore, the solutions offered that Islamic education should adapt to the technological development, building a strong academic culture and maximize the potential that there is such a stabilization concept operationally.